A cross-sectional study of demographic and morphologic features of rotator cuff disease in paraplegic patients - Akbar, Michael; Brunner, Manuela; Balean, Gabriel; Grieser, Thomas; Bruckner, Thomas; Loew, Markus; Raiss, Patric (Journal of shoulder and elbow surgery, 2011)
Background - This study analyzed the demographic and morphologic features of rotator cuff disease in paraplegic patients who presented with or without shoulder pain. - Methods - Clinical and magnetic resonance imaging examinations of both shoulders were performed in 317 paraplegic patients. Mean age was 49 (range, 19-76) years. The level of spinal cord injury was between T2 and T7 In 54% of patients and between T8 and L3 in 46%. Constant scores were measured for all shoulders. Pain was analyzed using a visual analog scale. - Results - Rotator cuff tears were not present in 51%, were unilateral in 20%, and were bilateral in 29%. Age was older and duration of spinal cord injury was significantly longer in patients with bilateral tears than in patients without or with unilateral tears (P < .001). In patients with unilateral tears, a full-thickness rupture of the supraspinatus tendon was found in 67%, whereas a partial-rupture was detected in 33%. Of the patients with bilateral tears, 75% presented with a full-thickness rupture and 25% with a partial rupture. The mean Constant score was 76 (range, 37-98) in patients without cuff tears, 69 (range, 16-94) for patients with unilateral tears, and 64 (16-96) for patients with bilateral tears (P < .001). - Conclusions - Rotator cuff disease is common and correlates highly with age and duration of spinal cord injury, which underlines the theory of “wear and tear” in wheelchair-dependent patients.